ASSESSMENT OF THE RELATIONSHIP BETWEEN SERUM ALBUMIN AND GLUCOSE LEVELS IN HEALTHY, PRE-DIABETIC, AND DIABETIC INDIVIDUALS’ CASE-CONTROL OBSERVATIONAL STUDY - Kumari, Kanchan; sinha, Swati; singh, Ajay kumar; Vaidehi; Sahay, Yogesh Krishna (Student's Journal of Health Research Africa, 2024)
Introduction Diabetes mellitus is a metabolic disorder characterized by chronic persistent hyperglycemia. If it persists for a prolonged period, it may lead to microvascular and macrovascular complications. Several studies were done to estimate serum albumin in diabetes mellitus, and there is uncertainty about the relationship between serum albumin and diabetes. Aim and objectives The aim of this study is to compare serum albumin in normal, pre-diabetic, and diabetic individuals. Materials and methods Glucose estimation was done using the Glucose oxidase Peroxidase method, and Albumin estimation was done using the Bromocresol Green method in Pawapuri, Nalanda. Results A total of 160 cases of age between 30-80 years were selected out of which 40 each were healthy, pre-diabetic, diabetic with Glucose levels less than 300mg/dl and above 300mg/dl. The mean Serum albumin level with standard deviation in normal individuals was 4.63± 30, in pre-diabetic individuals was 4.38 ± 0.24, in diabetic individuals were 4.23 ± 0.41, in uncontrolled diabetic individuals were3.98± 0.35. There was a significant decrease in serum albumin in pre-diabetic, diabetic, and uncontrolled diabetic individuals from normal individuals. Conclusion There was an inverse relationship between serum Albumin and Glucose in diabetic individuals. By regular estimation of serum albumin in diabetic individuals, the development of complications in diabetic individuals can be delayed. Recommendation Regular estimation of serum albumin levels in diabetes and keeping serum albumin levels within normal limits is required to delay diabetic complication development.